PERANCANGAN SISTEM INFORMASI LEGALISIR DOKUMEN BERBASIS WEB DI FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Kurnia Fitri; Zulhendra Zulhendra; Denny Kurniadi (Universitas Negeri Padang, 2014)
The Student in a collage who have finish their study will get an academic document as a legal proof. The academic document it could be like an academic certificate, academic transcript, or teaching certificates. The document can be use for a complement if the alumnus want to get a job or continue the study to the higher level in a duplicate document that has a signature and stamp from the competent people. To get an endorsement of document in Engineering Faculty of Universitas Negeri Padang is still through the manual process and not computerized yet. Certainty about when the process has finish is not yet, because there isn’t system that provides information about i yet. Storage of data relating to the management all of process is still in the form of archives and files is stored or held by Administration Employee. Therefore, designed a system that can manage all of process that can give ease for all users. The application design of the web-based information system done using the programming language PHP (Hypertext preprocessing) and the MySQL database as well as the division level access use a username and password. A method of password encryption Message Digest 5 (MD-5) and session web system are use to provide security to the data and information. This information system give provide services in an order, payment confirmation, check the status, managing bookings and payments that can be accessed by online system. Additionally, data storage has been using a database that can be accessed easily by users. Keywords : Information systems, web, PHP, MySQL, MD-5 and session.